THE CONCEPT OF AL JAM’IYATUL WASHLIYAH EDUCATION: SYSTEMATIZATION AND INTERPRETATION BASED ON THE PERSPECTIVE OF EDUCATIONAL SCIENCE - Arie Wibowo, Kenny Agusto; Lubis, Saiful Akhyahr; Mukti, Abd (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The purpose of this study is to explore in depth the concept of education applied in Al Jam’iyatul Washliyah and how this institution has succeeded in integrating Islamic religious education with general science teaching to produce graduates who are noble and competent in various aspects of life. The methodology of this study uses a qualitative-interpretive approach, with data collection methods including interviews, observations, and documentation. Data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data presentation, and drawing conclusions. The subjects of the study consisted of leaders and teachers at Al Jam’iyatul Washliyah and documents related to their education system. The conclusion of this study shows that the Concept of Education in Al Jam’iyatul Washliyah does not only focus on mastering science, but also places religious values ​​as the main foundation in forming the character of students. This integrative education system is characterized by a balanced curriculum between the world and the hereafter, and the concept of education offered is able to answer modern challenges without ignoring the Islamic values ​​that are the core of the education.